The use of educational game design and play in higher education to influence sustainable behaviour. Issue 3 (6th March 2017) - Mercer, Theresa G.; Kythreotis, Andrew P.; Robinson, Zoe P.; Stolte, Terje; George, Sharon M.; Haywood, Stephanie K.
Abstract : Purpose: The purpose of this paper is to discuss a novel life cycle approach to education for sustainable development (ESD) where the students become "design thinkers". Design/methodology/approach: A case study on the creation, development and utilisation of educational games by university students is presented. The paper discusses the case study in the context of Kolb's experiential learning and dynamic matching model, Perry's stages of intellectual development and Beech and Macintosh's processual learning model. The data used were from questionnaire feedback from the pupils who played the games and students who designed the games. Further qualitative feedback was collected from local schools involved in playing the games created by the students. Findings: Overall, the students responded positively to the assessment and would like to see more of this type of assessment. They enjoyed the creativity involved and the process of developing the games. For the majority of the skill sets measured, most students found that their skills improved slightly. Many students felt that they had learnt a lot about effectively communicating science. The school children involved in playing the student-created games found them accessible with variable degrees of effectiveness as engaging learning tools dependent on the game. Originality/value: This paper contributes a new approach to ESD which incorporates learner-centred arrangements within a full life cycle of game creation, delivery, playing and back to creation. The games can be used as a tool for enhancing knowledge and influencing behaviours in school children whilst enhancing ESD capacity in schools. The assessment also helps forge important links between the academic and local communities to enhance sustainable development.